The Use Of Youtube Vlogs In Learning Speaking To Perform Descriptive Text - Fadillah, Ahmad; Herlina, Rina; Faridah, Didih (Journal of English Education Program (JEEP), 2024)
The development of computer and internet technology has greatly contributed to language learning. YouTube vlogging is a popular and influential medium for students, giving them a chance to express themselves, enhance their language abilities, and discover new talents YouTube vlog was one of the methods that could motivate students to learn more about English speaking skills. For students, they use social media in various situations in their daily activities. This study aims to find out students’ experiences and perceptions of speaking learning through YouTube Vlog. The data of this qualitative case study was collected through questionnaires and interviews Twenty (20) students of one of the Senior High schools in Ciamis were employed. The researcher used triangulation to analyze the data. The result, gathered from an interview and questionnaire, demonstrates that students strongly favor personal YouTube Vlogs as a means of self-expression and sharing experiences. A highly positive student respond to learning speaking through YouTube Vlogs because it fosters enthusiasm, motivation, and comfort in descriptive text performance.